Back Cover: Industrial RuO2‐Based Deacon Catalysts: Carrier Stabilization and Active Phase Content Optimization (ChemCatChem 3/2013). Issue 3 (22nd February 2013) - Amrute, Amol P.; Mondelli, Cecilia; Schmidt, Timm; Hauert, Roland; Pérez‐Ramírez, Javier
<x xml:space="preserve">Abstract</x> Stability is the key! The cover picture shows the technical RuO2/SnO2‐Al2O3 catalyst (2 mm pellets) for the gasphase oxidation of HCl to Cl2. This reaction is an attractive route to valorise byproduct HCl streams in the chemical industry and has been experiencing a strong revival since recent discoveries of durable catalytic materials have broken through to pilot and plant scales. In their Full Paper on p. 748 ff., J. Pbrez‐Ramrez, T. Schmidt, and co‐workers reveal the stabilizing effect of the nanocrystalline alumina binder on the tin oxide support. The fundamental understanding of this stabilization secures the longevity of the industrial catalyst and has enabled a four‐fold decrease in the ruthenium content while maintaining a high specific activity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>